Communicating with the European Resistance: an assessment of the Special Operations Executive's wireless facilities in the UK during the Second World War. (3rd May 2016) - Gregory, Derwin
Abstract : Summary : This article presents for the first time an examination of the Special Operations Executive's (SOE) UK-based communication facilities. Established in 1940, SOE was responsible for coordinating all acts of sabotage against the enemy overseas. This was only possible with the aid of a reliable communications link with the Resistance. By examining SOE's Home Stations, this article will demonstrate the value the organization placed in reliable wireless communications.